Hold : how to find, buy, and rent houses for wealth - Chader, Steve; Papasan, Jay. (New York : McGraw Hill, 2013)
A guide to finding, buying, and renting houses for wealth, with help to find the right property, analyze the numbers and the terms of the purchase, manage the tenants and the property, and grow wealth to achieve financial freedom.
Keywords: Real estate investment; House buying; Rental housing